Night Sleep Deprivation - Computational Analysis of Language Effects - Carvalho, Flavio; Guedes, Gustavo Paiva (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
Changes in our society have been contributing to the raising number of people who will be under the effects of night sleep deprivation. This can harms health in the physical, mental and social aspects. This research work is intended to evaluate if there are differences between the affective characteristics in entries posted in two different time intervals, analyzing psycholinguistic processes and dominant emotions associated to social network users, using the LIWC in portuguese. In this preliminary study, it was possible to show a small difference in emotions expressed by users who posted between 6pm-23:59 and users who posted between 0am-5:59am.